Investigating Preservice Science Teachers’ Cognitive Structures on Environmental Issues - Zeynep KIRYAK; Bahar CANDAŞ; Haluk ÖZMEN (Universitas Pendidikan Indonesia, 2021)
Environmental knowledge and awareness of individuals affect their attitudes and behavior toward the environment. In this regard, it is essential to specify how environmental issues are interpreted in individuals’ cognitive structures. This study aims to investigate preservice science teachers’ cognitive structures on environmental issues. The study was conducted with 78 third-year preservice science teachers. The data were collected through a word association test that contains eight stimulus words about environmental problems and protecting the environment. Global warming, greenhouse effect, radiation, and acid rain were chosen for environmental problems; recycling, waste disposal, sustainability, and solar energy were selected for protecting the environment. Besides, preservice science teachers were asked to write a sentence for each stimulus word. Two concept networks were created based on the cut-off point method for the word association test, and content analysis was used for sentences. Besides, by comparing the data obtained from the concept networks and sentence analysis, an attempt was made to obtain more in-depth information. It is concluded that preservice science teachers focused on daily life rather than scientific facts about environmental issues. In this respect, new courses such as Green Chemistry may effectively eliminate alternative conceptions and raise awareness on environmental issues.